Actuators: Electrically and Sunlight‐Driven Actuator with Versatile Biomimetic Motions Based on Rolled Carbon Nanotube Bilayer Composite (Adv. Funct. Mater. 44/2017). (22nd November 2017) - Hu, Ying; Liu, Jiaqin; Chang, Longfei; Yang, Lulu; Xu, Aifeng; Qi, Ke; Lu, Pin; Wu, Guan; Chen, Wei; Wu, Yucheng
Abstract : Inspired by the common flicking finger motion, Ying Hu, Jiaqin Liu, Wei Chen, and co‐workers describe in article number1704388 a novel soft jumping robot based on the rolled carbon nanotube/polymer bilayer actuator with the two ends serving as thumb and middle finger, respectively. Upon light irradiation, this soft robot can jump up, accompanied by somersaults in the air, due to the energy accumulation and instantaneous release.